2019
DOI: 10.1016/j.stemcr.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

WDR5, BRCA1, and BARD1 Co-regulate the DNA Damage Response and Modulate the Mesenchymal-to-Epithelial Transition during Early Reprogramming

Abstract: Summary Differentiated cells are epigenetically stable, but can be reprogrammed to pluripotency by expression of the OSKM transcription factors. Despite significant effort, relatively little is known about the cellular requirements for reprogramming and how they affect the properties of induced pluripotent stem cells. We have performed high-content screening with small interfering RNAs targeting 300 chromatin-associated factors and extracted colony-level quantitative features. This revealed five mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…It is well known that WDR5 forms the histone H3 lysine 4 methyltransferase complex with mixed lineage leukaemia (MLL, MLL1-4) and promotes RNA polymerase II-dependent transcription activation (40). In addition, it was recently suggested that WDR5, BRCA1 and BRAD1 were functionally connected to suppress DNA damage during reprogramming (41). ZMYND8 was reported to play roles in activating transcription and promoting HR via multivalent binding to chromatin, including histone H4 acetlylations (30,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that WDR5 forms the histone H3 lysine 4 methyltransferase complex with mixed lineage leukaemia (MLL, MLL1-4) and promotes RNA polymerase II-dependent transcription activation (40). In addition, it was recently suggested that WDR5, BRCA1 and BRAD1 were functionally connected to suppress DNA damage during reprogramming (41). ZMYND8 was reported to play roles in activating transcription and promoting HR via multivalent binding to chromatin, including histone H4 acetlylations (30,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we performed a high-content siRNA screen, targeting 300 chromatin-associated factors during early reprogramming ( Fig. 1A) [23]. We hypothesized that the onset of reprogramming would be associated with colonylevel phenotypic changes and that these changes are affected upon gene perturbation.…”
Section: High Content Screening Reveals Early Reprogramming Disruptiomentioning
confidence: 99%
“…Using this data from two orthogonal screens, we identified strong phenotypic similarities between NCOR1 and OCT4 knockdowns. We have identified functional interactions from knockdowns showing similar phenotypes before [23,24]. Here we characterize the relationship of NCOR1 and OCT4 in early reprogramming.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These compounds are commonly used to facilitate reprogramming and pluripotent cell culture (Dakhore et al, 2018) and iPSCs generated in this manner are developmentally fully competent (Amlani et al, 2018). 3c reprogramming yields approximately 50 times more stable iPSC colonies than basal reprogramming and does so in a shorter period of time (six rather than twelve days of OKSM expression) (Penalosa-Ruiz et al, 2019;Saunders et al, 2017;Schwarz et al, 2018;Stelzer et al, 2015;Vidal et al, 2014). We therefore speculated that 3c might enhance iPSC formation by counteracting H3K9 methylation more efficiently than OKSM factors alone.…”
Section: Context-dependent Roles Of Ehmt1/2 Activity During Mouse Fibmentioning
confidence: 99%